ANALYSIS OF THE INNOVATIVE PRACTICES AT CONSTRUCTION INDUSTRY - Schreiber, Dusan; Pinheiro, Ivan Antônio (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
The complexity that has characterized the market relations, especially in the last two decades, with an ever increasing demand for innovative products and processes, has reflected even more in the traditional activities, such as the building sector. Although traditional, that segment has undergone many changes in the business model as a result of major technological advances, requiring companies to adapt to the new conditions, incorporating new technologies, materials and developing new processes, considered innovative. With the purpose of studying in depth this process a research with a qualitative single case study was conducted in an industrial building company, located in the metropolitan area of Porto Alegre, through in-depth interviews, analysis of the narratives and of documents. The results showed characteristics that required a specific design of the strategy, management practices and coordination of organizational resources, which allowed the company to become a reference in the sector.